OHP-069 Retrospective Study About Patients with a Stoma and Their Needs in the Health District of Patti (Messina). (12th March 2013) - Coppolino, S; Federico, F
Abstract : Background: Serious conditions of the bowel and bladder often require the formation of a stoma. It is estimated that 650, 000 people in Europe live with a stoma. A person with a stoma not only needs post-operative medical care, but also appliances and accessories to increase his quality of life. In the Local Health Authority (LHA) of Messina appliances and accessories are given, for free, every month by the Hospital/District Pharmacies. Purpose: To point out, for the Health District (HD) of Patti, which is one of seven HDs in the LHA of Messina, the number of patients with a stoma, the types of appliances and accessories used, and with what difficulties we assist patients. Materials and Methods: Through the retrospective interrogation of an administrative database it was possible to assess the number of patients with a stoma who live in the HD of Patti and, particularly, those who received appliances and accessories from 01/01/2011 to 31/12/2011. For each patient the gender, age, kind of stoma, type and amount of appliances and accessories were recorded. All data gathered were analysed with 'Statistica' software. During the delivery of devices patients were also interviewed about problems they had experienced. All answers were collected and reviewed anonymously. Results: 70 patients were recorded, mainly with a colostomy. The incidence in the HD population was 1:715 inhabitants. 55.7% of patients were males and the average age was 74.3 years [39, 94]. There was no difference between the number of patients with a one or a two-piece appliance. Closed appliances are most commonly used; 75% of patients had experienced at least one appliance leakage/year; 57.15% needed adhesive paste, 36% a skin protection barrier. Only 10% had difficulty in removing the stoma appliance causing skin stripping and ulceration. Conclusions: In the Patti HD hospital pharmacists can play a role in supporting and guiding patients and their carers by providing information, education and counselling on how to best manage their stoma in daily activities, in order to achieve an acceptable quality of life. No conflict of interest.